2010
DOI: 10.1258/jhsrp.2009.009035
|View full text |Cite
|
Sign up to set email alerts
|

Can a health forecasting service offer COPD patients a novel way to manage their condition?

Abstract: Patients found the automated interactive calling, combined with a health risk forecast, both viable and useful, welcoming the information and tools it offered. In many cases, it added to patients' understanding of their illness and promoted better self-management. Future research should focus on the potential impact of the service in terms of health outcomes and cost-effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…2 Qualitative data show that people receiving the forecast service felt empowered by it, and as a result had a sense of control over their condition as well as making them feel cared for. 31 These data also indicate that it is most beneficial for those who are ready to act in response to the automated calls, suggesting that when using the service in routine practice offering it to patients on an `opt-in' basis is likely to be the most successful way of implementing it.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…2 Qualitative data show that people receiving the forecast service felt empowered by it, and as a result had a sense of control over their condition as well as making them feel cared for. 31 These data also indicate that it is most beneficial for those who are ready to act in response to the automated calls, suggesting that when using the service in routine practice offering it to patients on an `opt-in' basis is likely to be the most successful way of implementing it.…”
Section: Discussionmentioning
confidence: 93%
“…Previous work has shown that nearly 90% of people receiving alert calls felt that they provided an important reminder at times when the prevailing weather conditions might present an increased risk to their health; one third of patients reported that they had sought a repeat prescription as a result of receiving an automated call, and one in five indicated they took some other remedial action such as turning on their heating, obtaining extra supplies of food, or avoiding unnecessary trips outdoors. 31 By encouraging behaviours such as staying at home or keeping warm, the alert call may reduce exacerbation rates by reducing the risk of acquiring infections, 32 the most common triggers. 33,34 However, the forecast and alert call may potentially have a greater role in reducing the impact of infections by ensuring that patients have sufficient medication and reminding them of the importance of prompt treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital admission rates for a number of conditions, most notably in respiratory and cardiovascular disease [3][4][5], have been linked to variations in the weather, and it is well established that trauma workload displays significant seasonal variation [6,7]. Weather forecasts are used to good effect in the commercial sector to predict consumer demand; a reliable predictive model in healthcare might enable targeting of high risk groups for intervention and effective planning of hospital staff levels [8][9][10]. Moreover, the recent trend toward networks for major trauma and centralisation of care means that relatively small changes in the incidence of trauma resulting from adverse weather conditions may lead to shifts in workload at major trauma centres sufficiently large to justify adding weather forecasts to resource planning [11].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, there are reported challenges associated with realising the acclaimed benefits of a health forecasting scheme, 10,11 even though successes have equally been documented. 12 Forecasting health events for health service provision, however, has the potential to have a more far reaching public health effect than simply mitigating adverse health events in individuals at known risk. 3 Health service providers can also be alerted to a likely increase in demand for services.…”
mentioning
confidence: 99%